The influence of natural environmental factors on benthic diatom communities from the Windmill Islands, Antarctica - Cunningham, LK; McMinn, A (Phycologia, 2004)
The species composition of benthic diatom communities responds rapidly to environmental change. At four shallow benthic sites in the Windmill Islands, Casey, East Antarctica, redundancy analysis indicated that changes in sediment grain-size, light availability and water depth account for 30% of the variation observed in the relative abundances of diatom taxa. The amount of mud (< 63 m) present within the sediments explained 18% of the variation in the relative abundances of diatom species observed in samples from all four locations. Within two locations, the amount of mud present explained 25% or more of the total variation in relative species abundance observed. Differences between locations explained 28% of the variation observed in relative species abundance; however, the majority of this was due to changes in grain-size, light availability and depth between the locations. It is unclear what other parameters contribute to observed differences between locations.